Chapter 12 Conclusions - Andresen, Maike (Taylor & Francis, 2020)
This conclusion presents some closing thoughts on the concepts covered in the preceding chapters of this book. The book discusses the impact of the 'home country' in self-initiated expatriates (SIEs) research. It describes the role of international human resource management (IHRM) in the management of SIEs and point out that little attention has been paid to the opportunities there are for IHRM to play a significant role in supporting SIEs in their careers. The book discusses how cultural distance between the home and the host country impacts expatriates' willingness to relocate abroad. It also discusses a rather new topic: how the language competence of SIEs impacts their foreign experience. The book utilizes stage models of life, career, and family as well as the social chronology framework to identify major elements and processes of the career transition of SIEs.